Penggunaan Teknologi Informasi dan Komunikasi (TIK) Dalam Pembelajaran Bahasa Inggris Pada Madrasah Aliyah Di Nganjuk - Maqbulin, Arjunina (Balai Diklat Keagamaan Surabaya, 2020)
ABSTRACT Recently, technology is a part of every ones’ life. This case also influences the education. Right now, teachers also involve technology in their teaching. This research aimed at finding the answer of to what extend English teachers at Islamic senior high schools in Nganjukhave used Information and Communication Technology in their teaching, teachers’ perception, and the problems they faced. The data were collected from English teachers who joined MGMP; a kind of English teachers’ organization for English teachers professional development in Nganjuk. The method used in this research is qualitative. This research is a kind of survey design. Questionnaire was used to collect the data. Descriptive analysis was used to analyze the data. The finding of this research revealed that majority of English teachers have used ICT in their teaching eventhough they did not use them optimally due to some problems, the data shows that 43% of the participants have used ICT, while 39% of them just sometimes use it, and 18% of them do not use it. The next finding is about teachers’ perception. This research showed that teachers have good perception about the use of ICT, 73% of the participants agreed that the use of ICT can make students more active in the classroom. The common problems they faced were the lack of facility and access, and lack of competence in using the technology. It is suggested that the school stakeholders evaluate the policy about the use of ICT in their schools. Then, English teachers’ organization trough MGMP should be optimized to upgrade teachers’ capability in using ICT for their teaching. Key words : technology, English , Islamic Senior High Schools.